Entrepreneurship Inclination among UUM Graduates - Yahya, Zaid Sameer (2010)
This study is undertaken to determine the factors that motivates graduates to be inclined to entrepreneurship. The main objectives of the study were to assess the level of significance of the four factors in determining the possible inclination of the graduates to entrepreneurship. The variables were monetary rewards, security, independence/autonomy and the intrinsic value. The study focused on the graduates from the Universiti Utara Malaysia. Pearson correlation analysis was used to test the research hypothesis. Multiple regressions analysis was used to test objective five in the study. A total of 191 responses were obtained from the respondent through the distribution of questionnaire. The finding shows that there were significant relationship between monetary motivation, independence/autonomy, intrinsic rewards, and security with entrepreneurship inclination. The result from multiple regression analysis shows that independence/autonomy (B=.419) is the strongest variables, followed by intrinsic rewards (B=.327) and monetary rewards (B= .152). The implication of this study suggests that there is a need for more graduates to be encouraged to engage in entrepreneurship with available of monetary benefit. The study further suggests that future study on entrepreneurship motivation should be far reaching in areas like culture.